Estación de trabajo ergonómica considerando las medidas antropométricas para prevenir las malas posturas y generar confort en los niños de Primer Año de Educación Básica de la Escuela de Educación Básica Estados Unidos del Cantón Riobamba, Parroquia Quimiag, Comunidad Balcashi. - López Rubio, Cármen Elisa (2016)
In the Postgraduate Institute of the “Universidad Nacional de Chimborazo” ergonomic work station was designed considering anthropometric measures to prevent bad positions in order to give comfort to children of first year of basic school education at school "Estados Unidos" in Riobamba, Quimiag, Balcashi community, the kind of research is bibliographic, field, of social intervention, applied, explanatory cross, with an exploratory, descriptive, correlational design, for getting information a survey was focus on teacher and some parents. It is applied in two steps before and after learning about the characteristics of the anthropometric measures and their benefit in the design of workstations, the sound level meter equipment was used, instrument that determines the different sound levels that are exposed by children during their school day, Light Meter and equipment to determine lighting levels surroundings in work. 17 anthropometric measurements were analyzed, after that they are generalized to get measurements for designing ergonomic work station. To prove the general and specifies hypothesis, the chi-square test was performed and the results were determined that the anthropometry measures influence the improvement of bad position and comfort of children in basic education of school “Estados Unidos” in Quimiag community Balcashi.